Increasing Awareness of Waste Management Through Environment-Based Education in Kebon Bongor Hamlet, Lembar Village: Peningkatan Kesadaran Pengelolaan Sampah Melalui Edukasi Berbasis Lingkungan Di Dusun Kebon Bongor Desa Lembar - Aying Alfaris Tosin; Diana Aulia; Dinnatul Kamilah; Abdul Hafis (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
Waste management has become a growing concern in rural coastal areas of Indonesia, including in Kebon Bongor Hamlet, Lembar Village, West Lombok Regency, where the accumulation of household waste particularly organic waste has led to environmental degradation and declining community health. This study aims to analyze the effectiveness of environmental education programs implemented in the area as an effort to improve community awareness and sustainable waste practices. The research employed a qualitative descriptive method through observation, interviews, and documentation to explore community participation and behavioral changes. The program integrated four main activities: mangrove planting to strengthen coastal ecosystems, establishment of a reading corner to enhance environmental literacy, socialization and demonstration of stacked buckets as a practical household composting technique, and the production of liquid organic fertilizer (POC) from organic waste to support local sustainable agriculture. The results indicate a notable improvement in community awareness, knowledge, and behavior regarding environmentally friendly waste management. Moreover, the program fostered active community participation in environmental conservation and sustainable living practices. The study concludes that environmental education combined with direct practical engagement is more effective in promoting social transformation and environmental responsibility at the grassroots level. These findings suggest that similar integrative approaches can be replicated in other rural areas to strengthen environmental literacy and encourage sustainable waste management.